Clarification of Zamia acuminata and a new Zamia species from Coclé Province, Panama - Lindström, Anders J.; Calonje, Michael; Stevenson, Dennis; Husby, Chad; Taylor, Alberto (Phytotaxa, 2013)
Zamia acuminata has remained an obscure, poorly understood species for over a century due to possibly misinterpreted or erroneous locality data on the unicate sterile type specimen, a very brief protologue description, the misidentification of the plants from El Valle de Antón in Panama as Z. acuminata, and the erroneous determinations of plants of Z. acuminata from Costa Rica as Z. fairchildiana. Recently collected material from San José Province in Costa Rica is here determined to be identical to the single sterile leaf material of the holotype of Zamia acuminata. We consider Z. acuminata to be a Costa Rican endemic species restricted to the western Talamanca mountain range in San José Province, and that the Zamia from El Valle de Antón in Panama, which has previously been referred to as Zamia acuminata, to be a new species, here described as Zamia nana.